Community Conversations on Relationship Violence: Town Variations in Prevention Perceptions through Concept Mapping. Issue 3 (9th January 2021) - Ast, Roxanna S.; Banyard, Victoria L.; Burnham, Jessica; Edwards, Katie M.
Abstract: To further develop domestic and sexual violence (DSV) prevention strategies at the community level requires an understanding of how community members in towns think about prevention. Using concept mapping, this study sought to better understand community members' perspectives about what DSV prevention strategies would be most feasible, most effective, and generate the greatest community support within their town. Data were collected across four rural Northern England towns. Participants (>90% White) in each town (total sample size = 119) brainstormed, sorted, and rated between 67 and 90 statements per town ( x̅ = 75). Based on the results, a 5‐cluster solution of school settings, conversations, individual direct action, community building, and community awareness was identified across all four towns as DSV prevention strategies with one town identifying an additional cluster solution of governance. Despite identifying similar prevention strategies, participants from each town rated these clusters of strategies differently on how feasible, effective, and supported they would be in their community. Overall, our results suggest that there were interesting consistencies across four towns in a similar geographic region in terms of how DSV prevention was described. However, individual communities differed in their views of the feasibility and acceptability of the different strategies. These results suggest that different strategies and higher‐level actions may be required to address and prevent DSV within different towns and communities and that community narratives can clarify which specific strategies may encounter fewer barriers to implementation. Highlights: This study uses concept mapping to gather collective perspectives on DSV prevention strategies. This study focuses on data collected across four rural Northern England towns. Participants across four towns identified similar cluster solutions for prevention strategies. Despite geographical similarities, towns require prevention initiatives tailored to their community. Concept mapping can be used as an effective assessment tool to capture variations within communities.